E-Administration as an Approach to Improving the Academic Performance of Law Faculty Members: An Experience at the University of Misan - Reyath Thea Azeez Alsafo; Mohammed Ahmed Waham; Mohammed Raoof Al-Musawi (International Journal of Economics, Management and Accounting, 2025)
The study sought to find the effect of E-administration in its various aspects on functional performance in the University of Misan/ College of Law. The target population was all members of the College of Law, N=40. The questionnaire was used as a tool for data collection, and distributed to the research groups, of which 33) questionnaires were collected and statistically analyzed. Data Processing and Analysis The SPSS 26 software was used to process and analyze the questionnaire information to calculate the arithmetic mean, standard deviation, correlation coefficient, and impact coefficient. One of the very significant findings was that "there is a statistically significant relationship between the research variables, and this will lead to satisfactory results that would contribute to solving and handling the problems which the researched college may encounter. At the end of the research, it was concluded that the recommendations which was concluded for the need for (Continuous Updating of the Software of Electronic administration systems according to the needs of work).